Incidence of Post-Operative Pulmonary Complications in Patients Undergoing Cardiac Surgery with Low Tidal Volume Ventilation - Asif Hassan, Wasim Riaz, Saira Gul, M. Qasim, Zargham Ur Rehman, Zaigham, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: This study sought to determine if low-tidal ventilation during CPB was superior to a resting-lung strategy with no ventilation in terms of pulmonary complications following surgery. Study Design: This was a retrospective study. Place and Duration: This study was done at the Punjab Institute of cardiology, Lahore from 1st May 2021 to 1st Nov, 2022. Methodology: A total of 1348 patients were enrolled in this study following inclusion criteria. They were divided into two groups equally. SPSS version 24 was used to enter and analyzed collected data. For qualitative variables was presented in frequency(%). For quantitative variables i.e., age, height, weight, preoperative FEV1/FCV, tidal volume, PEEP, PaO2 and PaCO2 mean ±SD was calculated. Chi-square was applied to compare post-operative outcomes between the groups. P-value of <0.05 was taken as significant. Results: The mean age of the cases in Group A was 55 ± 9.08 while in Group B was 56 ± 9.19. There were 75% male and 25% females in Group A while 84% male and 16% females in Group B. In our data there were 67% diabetic and 59% smokers in Group A however 62% diabetic and 58% smokers were enrolled in Group B. Mean tidal volume given to Group A was 8.5 ± 1.8 while in Group B was 7.5 ± 1.3. Peak respiratory pressure in Group A was 18 and in Group B was 16. Mean perfusion time, cross clamp time and anesthesia duration was significant between the groups p-value 0.01. Mean tidal volume given to Group A was 8.5 ± 1.8 while in Group B was 7.5 ± 1.3. Peak respiratory pressure in Group A was 18 and in Group B was 16. Mean perfusion time, cross clamp time and anesthesia duration was significant between the groups p-value 0.01. Conclusion: This study found that continuing low tidal volume ventilation was not superior to no ventilation during CPB in terms of the rate of reintubation, pleural effusion, and pulmonary congestion, although there was a significant difference between pneumonia, atelectasis, and prolong ventilation. Keywords: PEEP, CPB, FEV1/FCV ,Pulmonary Complications, Ventilation, Tidal Volume